Effect of 8-week Aerobic Exercise on Undercarboxylated Osteocalcin and Beta Cell Function in Postmenopausal Women - Asieh Abbassi Daloii; Esmatalsadat Mousavi (Medical Laboratory Journal, 2016)
ABSTRACT